ANALISIS YURIDIS TERHADAP PROSEDUR PENYELESAIAN DAN PERTIMBANGAN HUKUM BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM SENGKETA PROPERTI: Studi Putusan BPSK Kota Batam Nomor 001/PK-ARB/BPSK/I/2021 - Yaomi Tachyata Masning Rhuina; Diki Zukriadi (Jurnal Ilmiah Advokasi, 2026)
Consumer disputes in the property sector often arise from discrepancies between building specifications and the terms outlined in the agreement, leading to potential losses for consumers. This research aims to analyze the dispute resolution procedure thru arbitration mechanisms at the Consumer Dispute Resolution Agency (BPSK) of Batam City and to examine the legal basis for the decision in BPSK Decision Number 001/PK-ARB/BPSK/I/2021, which resulted in the rejection of the consumer's lawsuit. The research method used is normative juridical with a case approach and a statute approach, utilizing a study of decision documents and relevant legal literature. The research results indicate that the dispute resolution procedures at BPSK have been implemented in accordance with the provisions of Law Number 8 of 1999 concerning Consumer Protection, with simple, fast, and efficient resolution stages. The legal considerations of the BPSK panel focused on the interpretation of the "red brick or equivalent" clause in the contract, the validity of the building permit, and the laboratory test results proving the conformity of the building material specifications. Based on these considerations, the panel decided to dismiss the consumer lawsuit. This decision also underscores the importance of legal certainty, procedural effectiveness, and a balance of legal protection for both consumers and businesses.Keywords:  Arbitration; BPSK; Consumer Protection